Radiation and Temperature Effects on Optical and Electrical Properties of Dyed Poly (Vinyl Alcohol) Organic Composites Containing Chlorine - Susilawati (2005)
The effects of radiation on dyed PVA-based organic blends containing chlorine have been studied for their potential applications in radiation dosimetry as well as in optical and electrochemical devices. The PVA-CH, PVA-TCA and PVA-TeE blends were doped with cresol red and blended separately with 23, 34, 45 and 57% CH and 20, 25, 30 and 35% TCA and TCE. The composite films were prepared by solvent-casting method and each film has been irradiated with y-rays at different doses up to 12 kGy. The dosimetric and optical properties have been studied using Raman spectrometer and UV-VIS spectrophotometer in the wavelength range of 200 - 800 nm. The electrical properties have been studied using LCR meter, an impedance analyzer in the frequency range from 20 Hz to 1 MHz.The dosimetric study has shown that the absorption spectra of the irradiated PVA-CH composite films change color from yellow to red, but for the irradiated PVA-TCA and PVA-TCE blends, the films change color from purple to yellow. The change in color is because of the lowering the pH in the films caused by the presence of acid generated by y-ray interaction with CH, TCA and TCE. The useful critical dose at changing colour increases linearly with decreasing CH, TCA and TCE compositions in the range of (5.2 - 8.9), (5.0 - 7.5) and (6.0 - 8.7) kGy for PVA-CH, PVA-TCA and PVA-TCE respectively. The indirect dose response obtained from the absorbance at the absorption peaks has resulted in the linear increase of the dose sensitivity parameter Do with the increase of CH, TCA and TCE compositions. This has been confirmed by the direct dose response obtained from a decrease in the intensity of C-CI bond of CH, TCA and TCE molecules due to radiation scission using Raman spectroscopy technique, which has resulted in the increase of Do with increasing CH, TCA and TCE compositions. The optical absorption study has revealed that the absorption coefficient a increases with photon energy that is higher than the absorption edges with decreasing dose in range of (4.62 - 5.08), (4.00 - 4.74) and (4.44 - 4.88) eV for PVA-CH, PVA-TCA and PVA-TCE respectively for decreasing blend composition. The exponential relationship between the absorption coefficient and photon energy revealed that decreasing of Urbach's energy or optical activation energy !ill with the increase of dose in the range of (0.69 - 0.64),(0.68 - 0.61) and (0.72 - 0.65) eV for PVA-CH, PVA-TCA and PVA-TCE respectively for increasing blend composition. The direct band gap energy Eg obtained decreases with the increase of dose in the range of (4.12 - 4.02), (5.04 - 4.56) and (5.07 - 4.90) eV for PVA-CH, PVA-TCA and PVA-TCE respectively for increasing blend composition. While the indirect optical band gap energy Eg decreases with increasing dose in the range of (4.05 - 3.64), (3.8 - 3.44) and (4.62 - 4.23) eV for PVA-CH, PVA-TCA and PVA-TCE respectively for increasing blend composition. These changes are attributed to the radiation effect on the optical transitions of electrons from donor atoms to acceptor atoms in the electronic structure of the composites. The conductivity-dose relation study revealed that increase in conductivity of the irradiated PVA-CH, PVA-TCA and PVA-TCE blends with increasing dose up to 12 kGy. The increase in the conductivity with dose is attributed to the increase of ionic carriers in the composites induced by radiation scission of CH, TCA and TCE molecules and also due to hydrolysis of water. The conductivity spectra consist of frequency-independent dc component and frequency-dependent ac component. The flat response of dc conductivity has been attributed to free ions and has Arrhenius type relationship with dose that resulted in dose sensitivity Do increases with increasing blend composition. The power law type response of ac conductivity has been attributed to hopping of ions trapped in the localized sites of the PYA matrix and resulted in frequency exponent s decreases with increasing blend composition. The conductivity-temperature relation study revealed that an increase conductivity of the unirradiated PVA-CH, PVA-TCA and PVA-TCE blends with increasing temperature up to 353 K. The increase of conductivity with temperature is attributed to the increase of free ion mobility due to thermal energy kT and possible more ions gained kinetic energy via the thermally activated hopping of charge carriers between trapping sites and phonon-assisted quantum tunneling through a barrier separating two equilibrium positions. The conductivity activation energy obtained decreases with the blend composition increases. The dielectric-dose relation study revealed that an increase of the dielectric constant E' of the composites with increasing dose, which is attributed to the orientation polarizations of dipoles in the polymer system. The increase in dielectric loss E" with increasing dose can be attributed to dielectric dipole relaxation and dc conductivity of free ions in the blends. The dose sensitivity Do obtained increases with increasing blend composition. The dielectrictemperature relation study revealed that an increase of the dielectric constant E' with temperature can be attributed to the increase in the ability of dipoles to rotate towards the applied field as the binding forces between ions and atoms become weak with increasing temperature in the so called free volume effect. The increase in E" value with temperature increase can be attributed to the dc conduction process where the charge carriers gained kinetic energy via the thermal energy kT, thus increase the mobility of the free ions and the dielectric loss value. The electric activation energy obtained decreases with the blend composition increases